Modeling, Analysis and Control of Chaotic Rucklidge System - Rusyn, V. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
This paper presents modeling, analysis and research of chaotic Rucklidge system based on programming interface that has been developed in LabView software environment. This study allows for generating and researching the main properties of chaotic Rucklidge system, focusing on time distribution of three chaotic coordinates and phase portraits. A range of the system parameter with which we can generate different period (controlled) attractors and a number of trajectories of chaotic Rucklidge system are also presented. The programming interface demonstrates the algorithm of masking and decrypt information carrier. .